Meritocracy, policy and pedagogy: culture and the politics of recognition and redistribution in Singapore. Issue 3 (26th May 2020) - Lim, Leonel; Tan, Michael
ABSTRACT: Ideas about merit and the associated notion of a meritocracy have long been drawn upon to frame and understand a range of issues central to education policy. Little attention, however, is given to how in practice and through the workings of policy, meritocracy functions as an ideology that is struggled over by various social groups and pedagogic agents. Focusing on classroom pedagogic practices in Singapore, this article explores the ways in which in an ostensibly meritocratic education system, teachers interpret and negotiate ideas about culture to engage their students in the system's low-progress tracks. We argue that these teachers are creatively resisting, even challenging official discourses of meritocracy and engaging in what Nancy Fraser calls struggles over recognition and redistribution.